1989
DOI: 10.1136/jmg.26.5.348
|View full text |Cite
|
Sign up to set email alerts
|

Fetal valproate phenotype is recognisable by mid pregnancy.

Abstract: Correspondence theory remains speculative as the animal studies have shown no evidence of strings or bands as the cause of the limb deficiency. If the vascular compromise occurred at the time of premature rupture of the membranes there would be adequate time for healing of lesions and resorption of amputations. Healing in the fetus is particularly fast and relatively non-scarring.7 It is likely that this child's limb defects were related to amnion rupture, and are not associated with Van der Woude syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In an effort to further delineate the phenotypic features of FVS, the English literature was reviewed from 1978-2000 to identify patients with FVS. Cases that did not have adequate phenotypic description were excluded [Stanley and Chambers, 1982;Oakeshott and Hunt, 1989;Lindhout et al, 1992;Hockey et al, 1996; Case 3] as well as cases that were exposed to VPA and other anticonvulsant treatment [Thomas and Buchanan, 1981;Gomez, 1981;DiLiberti et al, 1984 Cases 2,4,5;Chitayat et al, 1988 Cases 1,2;Ardinger et al, 1988 Cases 9-19;Serville et al, 1989Christianson et al, 1994Thisted and Ebbesen, 1993 Cases 12-17;Baggot et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to further delineate the phenotypic features of FVS, the English literature was reviewed from 1978-2000 to identify patients with FVS. Cases that did not have adequate phenotypic description were excluded [Stanley and Chambers, 1982;Oakeshott and Hunt, 1989;Lindhout et al, 1992;Hockey et al, 1996; Case 3] as well as cases that were exposed to VPA and other anticonvulsant treatment [Thomas and Buchanan, 1981;Gomez, 1981;DiLiberti et al, 1984 Cases 2,4,5;Chitayat et al, 1988 Cases 1,2;Ardinger et al, 1988 Cases 9-19;Serville et al, 1989Christianson et al, 1994Thisted and Ebbesen, 1993 Cases 12-17;Baggot et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to further delineate the phenotypic features of FVS, the English literature was reviewed from 1978–2000 to identify patients with FVS. Cases that did not have adequate phenotypic description were excluded [Stanley and Chambers, 1982; Oakeshott and Hunt, 1989; Lindhout et al, 1992; Omtzigt et al, 1992; Hockey et al, 1996; Case 3] as well as cases that were exposed to VPA and other anticonvulsant treatment [Thomas and Buchanan, 1981; Gomez, 1981; DiLiberti et al, 1984 Cases 2,4,5; Chitayat et al, 1988 Cases 1,2; Ardinger et al, 1988 Cases 9–19; Serville et al, 1989 Christianson et al, 1994 Cases 1,2; Thisted and Ebbesen, 1993 Cases 12–17; Baggot et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Ardinger et al (1988) verified and confirmed DiLiberti et d ' s (1984) description of FVS in 19 children prenatally exposed to VPA. The syndrome becomes apparent as early as at midgestation stage of development (Serville et al, 1989). Robert and Guibaud (1982) and their colleagues interviewed 146 mothers of infants with spina bifida in the Rhone-Alps region of France and observed an unusual number of them were epileptic and had used VPA during pregnancy.…”
Section: Human Studiesmentioning
confidence: 99%